Radiation damage alloys Ti-Ge and positron annihilation - Мукашев, К.М.; Яр-Мухамедова, Г.Ш.; Мурадов, А.Д. (Recent Contributions to Physics, 2016)
In article the possibility of applying method of positron spectroscopy for system titanium-germanium alloys structural defects studyingis discussed. Defects created by irradiation with charged particles. The positrons are sensitive to radiation defects due to influence on the electronic structure of metals. Knowing the behavior of the positron annihilation and change parameters, you can monitor and predict evolution of structural damage. Such information is crucial both in terms of fundamental problems of the radiation defects formation and accumulation, and from perspective of developing recommendations for their practical use.